The effect of taubah and biofeedback based drug addiction intervention program among school students - Urme , Binte Salam (2014)
Nowadays, drug addiction is a severe problem for the family, society as well as all over the world which is spreading rapidly, especially among the adolescent. Though Malaysia is a peaceful country, but it is not an exception of this social disease.To date, there has not been much research conducted on the use of taubah protocol and biofeedback technique to reduce the drug addiction. According to Islamic law, drug addiction is a sin and the Muslim who used it, is a sinner. In Islam, spiritual activity such as through taubah a connection can be made by the Almighty, which is performed to the perfection of an individual’s mind. In psychological and psychophysiological research arena, biofeedback is one of the rising and versatile research techniques. To reduce this social disease taubah and biofeedback could be an effective alternative than the commonly used intervention programs such as motivational program, clinical study and training. In this study, 40 male school students aged 13–18from different schools in Kuantan area, Pahang, Malaysia were randomly selected as the intervention group and control group, where the number of respondents in each group was 20. They were treated with taubah protocol to change their psychophysiological responses which had been measured through biofeedback (GSR and HRV). Each intervention participant received five steps of taubah protocol of 30 minutes. Results of two-way repeated measures ANOVA indicated that there were significant group x time interaction effects of attention and cognitive flexibility. The intervention participants also showed significant reduction on depression, anxiety, and stress (all p < 0.01). Within-group improvements were also found for the training participants psychophysiological and emotional performance. Moreover, the intervention group showed a significant increase in ACS, LF activity, and GSR percentage change. Similar significant results did not exist in the control group. The findings of this study depicted that taubah and biofeedback effects significantly changed the cognitive, emotional and psychophysiological conditions which eventually reduced the addiction